RHETORICAL MOVES AND GENRE DEVELOPMENT IN SOFT SCIENCE RESEARCH ARTICLE ABSTRACTS - Isti Tri Wahyuni; Wawan Gunawan; R. Dian Dia-an Muniroh; Eri Kurniawan (Indonesian EFL Journal, 2021)
Abstracts in journal articles serve to present brief and clear information regarding research which generally covers the issue raised, the objectives, the methodology used and findings of the research. Consequently, an abstract holds a notable function and is considered as the face of the journal because most readers read the abstract first before going on to read the full paper. The objective of this study was to qualitatively analyse and compare the rhetorical moves and genre development of abstracts in soft science research articles before and after training. Forty abstracts—20 abstracts before receiving an intervention and 20 abstracts after receiving an intervention—written by Indonesian scholars in the soft science field were employed as data. Hyland’s (2000) five-rhetorical move model was used to analyse the data. The findings reveal that there are differences and developments in the use of rhetorical moves in journal article abstracts after receiving an intervention. This study can be used as an overview or as a reference for future research in the discourse analysis field, especially the analysis of abstract.Keywords: abstract writing; moves analysis; genre development; discourse analysis.